1998
DOI: 10.1021/ja980741o
|View full text |Cite
|
Sign up to set email alerts
|

Surface Infrared Studies of Silicon/Silicon Oxide Interfaces Derived from Hydridosilsesquioxane Clusters

Abstract: Hydridosilsesquioxane-based model systems have been developed over the past five years to help elucidate the structure and reactivity properties of silicon/silicon oxide interfaces. In this paper, the assignment of infrared bands as Si−O or Si−H derived is explored via deuterium labeling studies. In particular, the issue of the presence of adventitious water in the model interfaces is directly addressed via the chemisorption of deuterated-spherosiloxane clusters (D8Si8O12) onto clean Si(100). The experiments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…The monovertex attachment model contains the following key propositions: (1) the cluster cage remains intact, (2) the cluster is activated at one of the Si-H vertices, and (3) the cluster bonds to a Si dimer atom via a single Si-Si bond. [9][10][11][12] The cracked cluster model features Si-O bond scission along a cluster cage edge, resulting in a bridged bonding configuration across a Si dimer. 13,14 For these models, the Si 9 H 12 cluster was employed to simulate the silicon surface dimer to which the cluster is bonded.…”
Section: Model Of the Sample Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…The monovertex attachment model contains the following key propositions: (1) the cluster cage remains intact, (2) the cluster is activated at one of the Si-H vertices, and (3) the cluster bonds to a Si dimer atom via a single Si-Si bond. [9][10][11][12] The cracked cluster model features Si-O bond scission along a cluster cage edge, resulting in a bridged bonding configuration across a Si dimer. 13,14 For these models, the Si 9 H 12 cluster was employed to simulate the silicon surface dimer to which the cluster is bonded.…”
Section: Model Of the Sample Surfacementioning
confidence: 99%
“…The structure of H 8 Si 8 O 12 clusters chemisorbed on Si͑100͒-2 ϫ 1 has been previously characterized using x-ray photoemission spectroscopy (XPS), 9,10 reflection absorption infrared spectroscopy (RAIRS), 11 and STM. 12 As a model system used to determine the XPS binding assignments for the study of amorphous silicon oxide, the veracity of many papers rests on the determination of the correct binding mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of this experimental apparatus are described elsewhere. 28 Experiments typically involved taking a background spectrum, performing the desired CVD and then taking a second spectrum. The ratio of this second spectrum to the background was then calculated to arrive at the final plot.…”
Section: -3mentioning
confidence: 99%
“…They found that the calculated features were totally inconsistent with the experimentally observed peaks at lower binding energies, and suggested that the actual surface structure may be "more complex." Though more related work on this system has been performed [7][8][9][10], this discrepancy between theory and experiment has not been resolved.…”
mentioning
confidence: 99%